The offender's narrative: unresolved dissonance in life as a film (LAAF) responses - Youngs, Donna (Legal and criminological psychology, 2016)
Purpose. A growing body of literature indicates the value of exploring the accounts offenders give of their lives. This raises questions about whether offenders’ narratives, distinctive from those of non-offenders, elucidate the identity and agency processes that facilitate continued offending. Method. To explore this, 61 offenders and 90 non-offenders described their life as a film (LAAF). Results. Significant differences between the two samples are revealed across content categories relating to Implicit Content, Explicit Processes, Complexity, and Agency. These relate to a central focus on criminality as a dominant aspect of identity, a generally negative undertone, a concern with the materialistic within the narrative and the significant, yet problematic nature, of relations with others. These four features capture a meta-narrative of Unresolved Dissonance sustaining offending. Conclusion. The findings open the way for the use of the LAAF in order to explore ways of resolving offenders Unresolved Dissonance, through reconstructing their narratives, complementing the Good Lives approach.